NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL DAUN YANG JATUH TAK PERNAH MEMBENCI ANGIN KARYA TERELIYE - Idaman, Putri Anggraini (Pendidikan Bahasa Indonesia, 2014)
This study aimed to describe the values of character education in the novel The Falling Leaves Never Hated Wind Works Tere Liye. These values are related to: (1) Religious (2) Work hard (3) Rewarding achievement (4) Friendly I communicative (5) Social Care. Formulation of the problem of this study are the values of character education is contained in the novel The Falling Leaves Never Hated Wind Works Tere Liye.The research is a qualitative research. The method used is descriptive method. The data inthis study are the words, phrases and dialogues related to the values of character education. Sources of data in this study is novel Falling Leaves That Never Hated Wind Works Tere Liye.Based on the analysis of the data found the values of character education contained in the novel The Falling Leaves Never Hated Wind Tere Liye work are: religious, hard work, recognize excellence, friendship I communicative, social care. From this analysis it can be concluded. The values of character education contained in the novel The Falling Leaves Never Hated the wind works Tere Liye is religious, cooperation, recognize excellence, friendship I communicative and social care last.